Effects of bypass-current and outer plasma current on the arc stability and melt pool behaviors during plasma-MIG hybrid arc welding. (October 2022) - Miao, Yugang; Wang, Ziran; Liu, Ji; Wu, Yifan; Zhao, Yuyang; Li, Chunwang
Abstract: In this study, the heat and mass transfer behaviors of the plasma-MIG hybrid arc welding process were fully investigated. A comparative analysis between numerical simulation and physical experiment was performed to further explore the effects of bypass-current and outer plasma current on the hybrid arc stability and melt pool behaviors during welding. The results show that under the same process parameters, compared with bypass-current, the plasma-MIG hybrid arc with outer plasma current has an entire higher temperature. Furthermore, the outer plasma current can significantly expand the hybrid arc shape and increase the flow velocity of the melt pool, which indicates an increase in the weld width and penetration. Moreover, with outer plasma current, high electromagnetic force and arc pressure can be achieved. The bypass-current can lead to an overall reduction of heat flux on the upper surface of the molten pool. The research work develops a new numerical model to quantify the effects of bypass-current and outer plasma current on the arc stability and molten pool behaviors during plasma-MIG hybrid arc welding, which has a significant contribution to further process optimization and continuous improvement.